(3SQ GdeZJHW aj hab GdeNeS GdNGdi GdhSWs - (3eMeO Hf CHj HcQ GdJhGfjs
(3ChdgG (B:s
(3hHYO adeG cGf Yde GdChaGb YdekG TQjakG ef CLd GdYdhe hChSWgG hef CMSfgG hCbQHgG Gdhab GdeNeS GdNGdj GdhSW hVYJ Ydjg fXekG hSejJg hWdH efi HYV GdENhGf TQMkG Ydjg s
(3BNQgG (B:s
(3fGbUI BNQgG , BNQ GdehLhO (B: (3aGFOI GSeg JYGdi (B" (3GdHGbi (B" : (3ef bQCg Cda eQI bVjJ MGLJg hcai geg hGSeg JYGdi (B" (3GdHOjY (B" : (3ef bQGA SHYjf Cda eQI bVi Gddg MGLJg s
(3GdfSNI eQbeIs
(3HgG BKGQ QWhHI TOjOI hCQVI hMhGagG eJBcdIs
(3fSNI egJQFI s
(3hHYV GdcdeGJ hGdSWhQ ajgG HGdMeQI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMQha h GdChaGbs